Pengaruh Lingkungan Kerja dan Beban Kerja terhadap Kinerja Karyawan di PT. Adira Semesta Industry - Sri Mulyeni; Anita Tri Aningsih (Journal Economic Excellence Ibnu Sina, 2023)
This study the authors explain the effects of the work environment and workload on the performance of employees of PT. Adira Semesta Industry, with a total sampel of 92 employees, data collection methode using a questionnaire with analysis using multiple regression and the results of a partial analysis of work environment variables have a positive and significant impact on employee performance. Workload variables have a significant impact on employee performance with respective influence sizes of 3,231 an 2,274 greater than the t table of 2,101. And the simultaneous test results show that the work environment and workload together have a positive and significant impact on employee performance at PT. Adira Semesta Industry with F value of 32,520 > F Table 17,406.